2003
DOI: 10.1007/s00534-002-0842-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival and prognostic factors in the surgical treatment for intrahepatic cholangiocarcinoma

Abstract: Analysis of the clinicopathologic factors influencing the survival after surgical treatment showed that the macroscopic type, surgical curability, lymph node metastasis, tumor size, and cancer-free margin were the most predictive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
125
4
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 20 publications
10
125
4
2
Order By: Relevance
“…In addition, our study confirmed previously reported prognostic factors in cholangiocarcinoma, such as macroscopic type, intrahepatic metastasis, lymph node metastasis, and histological classification (Yamamoto et al, 1998;Ohtsuka et al, 2002;Morimoto et al, 2003;DeOliveira et al, 2007). Expression of EGFR or HER2 is known to be a prognostic factor in some cancers (Gusterson et al, 1992;Nicholson et al, 2001), but no previous study has clarified the influence of these molecules on prognosis in cholangiocarcinoma (Ito et al, 2001;Altimari et al, 2003;Nakazawa et al, 2005), probably because cholangiocarcinoma is a relatively rare cancer and collection of a large cohort is difficult.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, our study confirmed previously reported prognostic factors in cholangiocarcinoma, such as macroscopic type, intrahepatic metastasis, lymph node metastasis, and histological classification (Yamamoto et al, 1998;Ohtsuka et al, 2002;Morimoto et al, 2003;DeOliveira et al, 2007). Expression of EGFR or HER2 is known to be a prognostic factor in some cancers (Gusterson et al, 1992;Nicholson et al, 2001), but no previous study has clarified the influence of these molecules on prognosis in cholangiocarcinoma (Ito et al, 2001;Altimari et al, 2003;Nakazawa et al, 2005), probably because cholangiocarcinoma is a relatively rare cancer and collection of a large cohort is difficult.…”
Section: Discussionsupporting
confidence: 80%
“…When compared with the mass forming type, those with intraductal growth type had a 0.25 times (95% CI: 0.11-0.57) lower risk of death, and those with the periductal infiltrating type had a 0.63 times (95% CI: 0.29-1.34) lower risk of death. These findings are almost the same as those in the study reported by Morimoto et al (2003). However, Guglielmi et al (2009) reported a rather different finding; patients with mass forming cancers had longer survival rates.…”
Section: Discussionsupporting
confidence: 87%
“…The poor prognosis is due to the anatomical position of the gallbladder and the delayed clinical presentation in most patients, primarily due to a lack of specific symptoms and low clinical suspicion. The only curative therapy for gallbladder carcinoma is surgical resection [3][4][5]. The goal of resection should always be total tumor extirpation with negative histologic margins.…”
Section: Introductionmentioning
confidence: 99%